Smartboard-Mediated CSCL Scripts to Improve Oral Communication in Eastern Indonesia: A Quasi-Experimental Study - Kaharuddin; Sitti Hajar; Zul Fadhli Al Alim; Andi Kaharuddin; Topanus Tulak; Ganjar Susilo; Devasis Pradhan (Jurusan Teknik Informatika dan Komputer, 2026)
Purpose – This study aims to challenge the